A Novel ESAT-6 Secretion System-Secreted Protein EsxX of Community-Associated Staphylococcus aureus Lineage ST398 Contributes to Immune Evasion and Virulence - Dai, Yingxin; Wang, Yanan; Liu, Qian; Gao, Qianqian; Lu, Huiying; Meng, Hongwei; Qin, Juanxiu; Hu, Mo; Li, Min (Frontiers in Microbiology, 2017)
The ESAT-6 secretion system (ESS) has been reported to contribute to the virulence and pathogenicity of several Staphylococcus aureus strains such as USA300 and Newman. However, the role of the ESS in community-associated S. aureus (CA-SA) lineage ST398 in China is not well understood. By comparing the ess locus of ST398 with the published S. aureus sequence in the NCBI database, we found one gene in the ess locus encoding a novel WXG superfamily protein that is highly conserved only in ST398. LC-MS/MS and Western blot analysis revealed that this protein is a novel secreted protein controlled by the ST398 ESS, and we named the protein EsxX. Although EsxX was not under the control of the accessory gene regulator (agr) like many other virulence factors and had no influence on several phenotypes of ST398, such as growth, hemolysis, and biofilm formation, it showed important impacts on immune evasion and virulence in ST398. An esxX deletion mutant led to significantly reduced resistance to neutrophil killing and decreased virulence in murine skin and blood infection models, indicating its essential contribution to the evasion of innate host defense and virulence to support the pathogenesis of ST398 infections. The function of this novel secreted protein EsxX might help us better understand the role of the ESS in the virulence and epidemic success of the CA-SA lineage ST398.